The organization of bachelor’s training in economics at the universities of Germany - Амеліна, Світлана; Дзюба, Ганна (Pedagogy of Higher and Secondary Education, 2013)
Amelina S. N., Dziuba A. I. The organization of bachelor’s training in economics at the universities of Germany. The article deals with the questions of professional training of bachelor of economics at the universities of Germany. A comparison of the two main programs for bachelor degree in economics is made. The content of undergraduate programs in the context of mandatory and optional modules is presented. The requirements for modular exams and undergraduate work are described. The features of the transmission of practices of future specialists are presented.